Internet Browsing - Hikmah Arfatul Jannah,; Sri Amelia R.Laoh,; Elisa Raup,; Tesalonika Pangkey,; Natasya Sumendah,; Febyola Mihkaella Monigir,; Safina Kobandaha,; Judea Rorong, (Student Scientific Creativity Journal, 2024)
One of the essential aspects of internet browsing is the existence of web browsers, software that enables users to access various websites and online resources. The objective of this study is to understand users' behavioral patterns when engaging in internet browsing activities across different digital platforms and to identify the positive and negative impacts of internet browsing on users' productivity and well-being in daily life. This study employs a qualitative descriptive method. The findings indicate that internet browsing has a significant impact on users' productivity and well-being, both positively and negatively. On the positive side, browsing can enhance work efficiency, support learning, and provide entertainment that helps reduce stress.